RANCANG BANGUN SISTEM PEMANEN ENERGI ANGIN EXHAUST FAN DENGAN PENGARUH JARAK TURBIN ANGIN SUMBU HORIZONTAL BILAH EXHAUST FAN - Mawadah Wr Febriyani; I Wayan Sukerayasa; Cokorde Gede Indra Partha (Jurnal SPEKTRUM, 2021)
Energy demand in Indonesia is increasing, especially in the realization of electricityconsumption which reached 20.18 TWh in July 2020. In fulfilling energy, Indonesia is stillsupported by fossil energy. Indonesia's fossil energy reserves continue to decline, so it isnecessary to increase the non-fossil energy, one of which is wind energy. Wind exhaust fanoutput is waste energy that has the potential to be developed as a micro-scale wind powerplant. The Design and Construction of the Exhaust Fan Wind Energy Harvesting System withthe Effect of the Horizontal Axis Wind Turbine Distance (HAWT) of the Exhaust Fan Blade hasbeen done, the test of this study determine the optimal output power of the generator byconsidering the exhaust fan performance. The test results show that the closest distance of 10cm produces maximum wind speed and power, but the optimal placement distance for theturbine designed is 20 cm with an output power of 1.50 Watt and an increase in exhaust fanconsumption power of 0.38, with the power that can be harvested is 1.50-0.38 = 1.12 Watt,greater than the other test distances.